2021
DOI: 10.1111/1755-0998.13327
|View full text |Cite
|
Sign up to set email alerts
|

A multitiered sequence capture strategy spanning broad evolutionary scales: Application for phylogenetic and phylogeographic studies of orchids

Abstract: With over 25,000 species, the drivers of diversity in the Orchidaceae remain to be fully understood. Here, we outline a multitiered sequence capture strategy aimed at capturing hundreds of loci to enable phylogenetic resolution from subtribe to subspecific levels in orchids of the tribe Diurideae. For the probe design, we mined subsets of 18 transcriptomes, to give five target sequence sets aimed at the tribe (Sets 1 & 2), subtribe (Set 3), and within subtribe levels (Sets 4 & 5). Analysis included alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 99 publications
(198 reference statements)
1
31
0
Order By: Relevance
“…It is further of interest that the genus Chiloglottis belongs to a subtribe (Drakaeinae) in which all genera are exclusively sexually deceptive (with the exception of some rare self-pollinating cases) and all fall within a well-resolved clade on a long branch of the diverse predominantly Australasian tribe the Diurideae ( Peakall et al, 2021 ). Thus, it is likely that the complex chemical and genetic basis of floral color mimicry may have been finely tuned by a long evolutionary process in these sexually deceptive orchids ( Weston et al, 2014 ; Peakall et al, 2021 ). This is in contrast with some of the well-known flower color polymorphisms found within natural populations ( Streisfeld and Rausher, 2011 ; Kellenberger et al, 2019 ), and even the flower color changes associated with key pollinator shifts that are often mediated by relatively simple genetic changes restricted to a few genes within the anthocyanin and flavonol glycoside pathways ( Wessinger and Rausher, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is further of interest that the genus Chiloglottis belongs to a subtribe (Drakaeinae) in which all genera are exclusively sexually deceptive (with the exception of some rare self-pollinating cases) and all fall within a well-resolved clade on a long branch of the diverse predominantly Australasian tribe the Diurideae ( Peakall et al, 2021 ). Thus, it is likely that the complex chemical and genetic basis of floral color mimicry may have been finely tuned by a long evolutionary process in these sexually deceptive orchids ( Weston et al, 2014 ; Peakall et al, 2021 ). This is in contrast with some of the well-known flower color polymorphisms found within natural populations ( Streisfeld and Rausher, 2011 ; Kellenberger et al, 2019 ), and even the flower color changes associated with key pollinator shifts that are often mediated by relatively simple genetic changes restricted to a few genes within the anthocyanin and flavonol glycoside pathways ( Wessinger and Rausher, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast with some of the well-known flower color polymorphisms found within natural populations ( Streisfeld and Rausher, 2011 ; Kellenberger et al, 2019 ), and even the flower color changes associated with key pollinator shifts that are often mediated by relatively simple genetic changes restricted to a few genes within the anthocyanin and flavonol glycoside pathways ( Wessinger and Rausher, 2012 ). It will be of interest in future research to determine whether sexually deceptive lineages of more recent evolutionary origin than Chiloglottis (e.g., Caladenia , Caladeniinae; Diurideae) ( Peakall et al, 2021 ) exhibit floral color adaptions based on simple genetic changes, as one might expect at the early stages in the evolution of sexual deception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and Caleana R.Br. are sister genera within the subtribe Drakaeinae and molecular studies have confirmed their close ancestral relationship (Miller & Clements 2014, Peakall et al 2021. Differences in their morphology (Blaxell 1972) and pollination syndromes (Cady 1965, Bower 2014 support their status as distinct genera.…”
mentioning
confidence: 92%